Prinsip Dasar dan Penerapan Pendidikan Unggah-Ungguh dalam Kearifan Budaya Jawa - Retnaningsih, Aritiyas Panca; Suryosumunar, John Abraham Ziswan (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2024)
The life of Javanese society is inseparable from the orientation of maintaining harmony in every social bond. One of the most important social bonds is the family. The family becomes the primary vessel for shaping the character and identity of each individual. In Javanese cultural wisdom, this is closely tied to character education or unggah-ungguh within the family. The researcher seeks to examine the education of unggah-ungguh using the philosophical hermeneutic method to understand its principles and application. The data used comes from various literature sources, including journals, books, and other texts obtained through a literature review. The researcher’s study led to the following conclusions: 1) In unggah-ungguh teachings, the principles of unity and independence are emphasized to maintain harmony and social rootedness while upholding independence and the nobility of character. 2) The Javanese language serves as the primary medium for unggah-ungguh education, training individuals in refinement of character and sensitivity to the social context they face. 3) Proficiency in using the Javanese language correctly (bener and pener) influences the refinement of behavior of those who use it. This becomes a key factor in fostering harmony in social life, both within the family and in broader social contexts.